An 8P Theoretical Framework for Understanding Creativity and Theories of Creativity. (1st August 2021) - Sternberg, Robert J.; Karami, Sareh
ABSTRACT: This article presents an 8P theoretical framework for understanding creativity and theories of creativity. The 8Ps are purpose, press, person, problem, process, product, propulsion, and public. The article opens by distinguishing between a theory and a model, on the one hand, and a theoretical framework, on the other. It then considers briefly some of the theoretical frameworks for creativity that have been proposed in the past. Next, it describes the 8P theoretical framework and how it applies to understanding creativity and theories of creativity. The 8P framework suggests that most theories of creativity have been rather incomplete, dealing only with limited aspects of the phenomenon.